Perceptions of Infection Control Among Nurses Regarding Barriers: A Qualitative Study: Perceptions of Infection Control Among Nurses - Shoukat, Saffora; Ali, Afsar; Aziz, Zunaira (Pakistan Journal of Health Sciences, 2023)
Infection in healthcare facilities is an alarming public health problem in most growing countries. Hospital infections are the most significant worldwide complication of healthcare delivery. Objectives: To acquire a deeper understanding of infection control nurses' perspectives on the barriers regarding the infection control practices at the tertiary care hospitals Lahore. Methods: A qualitative exploratory research approach was utilized. Data was collected from the infection control nurses. Semi-structured interviews were used to collect the data from the 10 study participants through purposive sampling technique. Each interview was transcribed. The data were manually analyzed before being processed by NVIVO. Results: A thematic analysis was conducted to determine the themes and sub themes through Braun and Clark's (2006) concept of thematic analysis. The researcher identified three major themes and few minor. The major themes were organization related barriers, health care workers related barriers and patients and family related barriers. Organization lack of facilities was among the top barriers to infection prevention and control. Conclusions: Most of the participants had good and enough information regarding the infection prevention and control programs, but it doesn’t mean that these activities and implementations will be practiced in routine manners. Three major themes with different barriers were identified. Themes well explained regarding barriers in implementing infection control practices in both public and private hospitals.